Medical and Surgical Education Past, Present and Future - Tsoulfas, Georgios (IntechOpen, 2018)
The last century has witnessed tremendous changes in the education and training system of medical students, as well as medical and surgical residents, in short, our future physicians. This has been the result of the changes in the educational philosophy, the technology, and the needs of our patients, just to name a few. The challenge is to learn more about the various systems in medical education throughout the world and identify advantages and disadvantages, a process from which we can all (and most importantly our patients) benefit from. This book is a compilation of the experiences, thoughts, and "best-practice" advice of a panel of international experts on medical and surgical education.